Transition Metal Phthalocyanines as Nitrogen Oxydes Sensors - Anna Maria Paoletti; Giovanna Pennesi; Gentilina Rossi; Amanda Generosi; Barbara Paci; Valerio Rossi Albertini (Current Advances in Chemistry and Biochemistry Vol. 8, 2021)
Phthalocyanines are organic aromatic compounds, whose metal complexes are used in many technological and industrial applications, ranging from active element in catalysis and organic solar cells, photosensitizing substance in light therapies and dye for “denim” blue jeans. The present study is devoted to the description and comprehension of phenomena connected with the sensing behaviour towards NO2 of films of two transition metal phthalocyanines, namely titanium bis-phthalocyanine and ruthenium phthalocyanine. Spectroscopic, conductometric, and morphological features recorded during exposure to the gas are explained and the mechanisms of gas-molecule interaction are also elucidated. The investigation is performed by applying standard techniques, that is conductrometry and UV-Visible spectroscopy, together with an unusual one, the Energy Dispersive X-ray Reflectivity. Indeed, the latter turns out to be a powerful tool for monitoring morphological parameters, such as thickness and roughness, that are demonstrated to be sensitive variables for monitoring the exposure of thin films of sensor materials to NO2 gas.